Estresse ocupacional e absente??smo dos profissionais de enfermagem em um hospital p??blico de S??o Paulo - Oliboni, Maria Wilsa Cabral Rodrigues (2015)
The aim of this study is to investigate the relationship between occupational stress and absenteeism of nursing professionals who work in a public hospital in S??o Paulo. This study describes the general characteristics of the nursing team; assesses the psychosocial aspect at work; psychological and physical demand and job control through JSS questionnaire relating the stress level at work with the absenteeism of nursing professionals. The method used is classified as descriptive, quantitative and exploratory research, using techniques as documentary research and data collection. The data collected refer to the demographic characteristics of the nursing team professionals, as well as questions about absences and leaves. The sample consisted of 86 professionals. For allocation of scores we used a cut-off point obtained by the median for demand and control and medium for social support. Data analysis was performed by descriptive analysis of the sample and correlation testing of absence days and dimensions. It was also analyzed the dimension???s associations with socio-demographic data. The survey results showed that the dimensions demand and control features statistically significant correlation. Social support did not present significant correlation with control, but correlated with the demand. Considering the research participants professionals, 54% had high demand, 44% high control and 49% low social support. Comparing with the demand control model, we identified that the active work is considered a good work situation. In carrying out the associations of the dimensions with socio-demographic data we did not have statistically significant results. We concluded that despite not having found associations and correlations of the dimensions and socio-demographic data with absenteeism it does not mean it does not exist. Stands out as limiting factor of the search the fact that it has only been held in one institution acting in more women, the reason why it hinders us from fulfilling sex comparisons, in addiction due to collection of data on absences be self-related by professionals. As a suggestion for practice it is suggested that the institution carries out the control of absences and its reasons in a computerized form. We suggest that further researches be performed in hospitals with different characteristics of this study and at the same hospital this study after computerization of the absenteeism control. For comparative studies can be performed.